Academic Freedom and Its Constraints: A Complex History - Axelrod, Paul (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
Academic freedom has a long, complex history in Canada and elsewhere. For reasons that are at times justifiable and at times indefensible, academic freedom has been constrained in a variety of ways, and not only by institutional or political authorities. Using illustrations drawn from Canada and beyond, this article tracks the history and progress of academic freedom and takes stock of its status in the first part of the 21st century. It explores the origins of academic freedom, the evolving ways in which it has been qualified and even impeded, the particularity of Canadian approaches to its values and practices, and the ongoing challenges universities may face sustaining academic freedom in unsettled and unpredictable times.